The Victorians and old age - Chase, Karen, 1952- (Oxford : Oxford University Press, 2009)
This text studies the social and literary conditions which helped construct the experience of old age in the Victorian period.
Description based on print version record.
Includes index.
Keywords: English fiction -- 19th century -- History and criticism; Old age in literature; Older people -- Great Britain -- Social conditions -- 19th century